Modern architecture - Александр Кудрявцев (Проект Байкал)
Architects-modernists faced public protests against the destruction of the historical urban environment in the late 20th century. The urban defenders relied upon the Venice Charter, an international document stating that “restoration ends where hypothesis begins”. Nevertheless, at the beginning of the 21st century there appeared historical properties that synthesized contemporary architecture with architectural heritage and were adopted by expert society and public opinion.